Construction and applications of superhydrophilic surface based on ethylene-vinyl acetate copolymer/nitrile-butadiene rubber thermoplastic vulcanizate - Weiran Zhang; Yuan Gao; Ruotao Feng; Dazhi Zhu; Zhaobo Wang (eXPRESS Polymer Letters)
In this research, a straightforward template method was utilized to fabricate a superhydrophilic ethylene-vinyl acetate copolymer (EVA)/nitrile-butadiene rubber (NBR) thermoplastic vulcanizate (TPV) surface where the paper sheet was used as template. Organic modified montmorillonite (OMMT) powder was introduced in order to improve the superhydrophilic response rate of the TPV surface. Investigations were conducted to research the durability and the self-cleaning behavior of the TPV surface, as well as to explore its potential application in the separation of oil-water and oil-oil mixtures. Experimental results demonstrated that the EVA/NBR/OMMT TPV (mass ratio 20/80/7) surface molded with No. 1000 paper sheet exhibited the excellent superhydrophilic property, which could achieve a contact angle of 0.0° within 5.5 s and had a surface energy of 35.6 mN·m–1. The superhydrophilic surface displayed the remarkable durability and the evident self-cleaning behavior; moreover, it could exhibit the significant difference in the critical pressure data for various liquids, suggesting the promising application in the field of oil-water and oil-oil separation.